A study on the motorcycle helmets laws in ensuring the compliance of proper safety helmet usage in Malaysia / Azraii Azahari Abdul Gani, Abdul Karim Shamsuddin and Mohd Redzuan Othman - Abdul Gani, Azraii Azahari; Shamsuddin, Abdul Karim; Othman, Mohd Redzuan (2012)
From the literature review as well as the background of this proposal, it is apparent that the question on the enforcement of the Motorcycles (Safety Helmets) (Amendment) Rules 2010 is still lacking in maintaining the safety standards of helmets used by the motorcyclist in Malaysia. These rules were made by the minister by virtue of Section 88 of the Road Transport Act 1987.The law can only be effectively addressed by carefully examining the strength and the weaknesses of the current enforcement to identify the gaps that need to be filled. This study sets out to discover the issue of the safety standards of helmets used by the motorcyclist and the enforcement of the law itself in Malaysia. There are lacks of enforcement by the authority on this matter and we found that it may be fixed in order to strengthen the safety of the motorcyclist in Malaysia.